Wireless Automated Exhibition System: Convenient Mobility at Low Cost - Hirunwijitporn, Nirumol; Jongchanachavawat, Wirote; Bunyarittikit, Suphat; Mingmuang, Noppon; Roopkom, Ittipat; Katwattanakul, Anurak; Tabo; Kumngern, Peemongkol; Jongchanachavawat, Patchamon; Kaewpangkro, Sirawit (My University, 2025)
The application of wireless automatic exhibition system for event promotion facilitates the organization of exhibition-related activities by enabling automated control of exhibition displays. This system eliminates the need for allocating personnel to monitor the exhibition, thus reducing the cost of hiring exhibition attendants. From this research, it is possible to create a low-cost wireless automatic exhibition display system that is convenient for use in various events and exhibitions, especially when there are numerous booths involved. The system utilizes infrared sensors to detect visitors within a range of 90 cm, enabling accurate visitor counting. Once the desired number of visitors is reached, the exhibition will be displayed immediately. Additionally, the system can detect exiting visitors while the exhibition is ongoing. When the specified visitor count is met, the exhibition display will stop instantly. Due to these features, this wireless automatic exhibition system is affordable, easily portable, and suitable for various events and exhibitions. It is user-friendly and convenient for deployment.
Keywords: Automation; Embedded system; Exhibition system; Wireless communication; Wireless counting